Carrots and sticks : unlock the power of incentives to get things done - Ayres, Ian. (New York : Bantam Books, 2010)
The part-owner of StickK.com uses research into incentives and punishments to introduce the concept of'commitment contracts,' an easy strategy for setting and achieving goals that is already in use by successful companies and individuals across America. Ayres shares engaging, often astounding, real-life stories that show the carrot-and-stick principle in action, from the compulsive sneezer who needed a'stick' (the potential loss of $50 per week to a charity he didn't like) to those who need a carrot with their stick (the New York Times columnist who quit smoking by pledging a friend $5,000 per smoke . . . if she would do the same for him). You'l learn why you might want to hire a'professional nagger' whom you'll do anything to avoid- no, your spouse won't do!- and how you can'hand-tie' your future self to accomplish what you want done now. You'll find out how a New Zealand ad exec successfully'sold his smoking addiction', and why Zappos offered new employees $2,000 to quit cigarettes.
Thaler's apples -- Incentives versus commitments -- Losses loom large -- That nagging feeling -- Maintenance and mindfulness -- What commitments say about you -- Antonio's problems -- A commitment store.
Includes bibliographical references and index.
Keywords: Commitment (Psychology); Incentive (Psychology); Motivation (Psychology); Economics -- Psychological aspects